The Relatedness of Islamic Consumption Values with Responsible Consumption for Development (Case Study in Indonesia) - Lindiawatie - Lindiawatie; Dhona - Shahreza (Universitas Pendidikan Indonesia, 2023)
Improving consumption patterns that are responsible for development is very important to be done by everyone. Irresponsible consumption led to negative impacts on social and environmental life. Islamic consumption values are the solution. This study aims to determine the relatedness of Islamic consumption values and responsible consumption for development and to determine the implementation of the dimensions and principles of Islamic consumption that enable the realization of responsible consumption for development in the form of attitudes and perspectives. The method of research is by distributing questionnaires to Muslim communities in the Greater Jakarta area and outside Greater Jakarta. The result is that Islamic consumption values have a strong and significant relatedness with responsible consumption for development. Its implementation is in the form of being careful, careful, not rash, and controlling oneself when consuming something so as not to have a bad impact on social life and the environment. The implementation of Islamic consumption values means responsible consumption for development. Thus, Islamic consumption values support one of the SDGs agenda on Responsible Consumption.